Diagnostic and prognostic value of triglyceride glucose index: a comprehensive evaluation of meta-analysis - Sandeep Samethadka Nayak; Dona Kuriyakose; Lakshmi D. Polisetty; Anjali Avinash Patil; Daniyal Ameen; Rakshita Bonu; Samatha P. Shetty; Pubali Biswas; Micheal T. Ulrich; Negin Letafatkar; Arman Habibi; Mohammad-Hossein Keivanlou; et al. (Cardiovascular Diabetology, 2024)
Abstract Objective The present umbrella review aims to collate and summarize the findings from previous meta-analyses on the Triglyceride and Glucose (TyG) Index, providing insights to clinicians, researchers, and policymakers regarding the usefulness of this biomarker in various clinical settings. Methods A comprehensive search was conducted in PubMed, Scopus, and Web of Science up to April 14, 2024, without language restrictions. The AMSTAR2 checklist assessed the methodological quality of the included meta-analyses. Statistical analyses were performed using Comprehensive Meta-Analysis (CMA) software. Results A total of 32 studies were finally included. The results revealed significant associations between the TyG index and various health outcomes. For kidney outcomes, a high TyG index was significantly associated with an increased risk of contrast-induced nephropathy (CIN) (OR = 2.24, 95% CI: 1.82–2.77) and chronic kidney disease (CKD) (RR = 1.46, 95% CI: 1.32–1.63). High TyG index was significantly associated with an increased risk of type 2 diabetes mellitus (T2DM) (RR = 3.53, 95% CI: 2.74–4.54), gestational diabetes mellitus (GDM) (OR = 2.41, 95% CI: 1.48–3.91), and diabetic retinopathy (DR) (OR = 2.34, 95% CI: 1.31–4.19). Regarding metabolic diseases, the TyG index was significantly higher in patients with obstructive sleep apnea (OSA) (SMD = 0.86, 95% CI: 0.57–1.15), metabolic syndrome (MD = 0.83, 95% CI: 0.74–0.93), and non-alcoholic fatty liver disease (NAFLD) (OR = 2.36, 95% CI: 1.88–2.97) compared to those without these conditions. In cerebrovascular diseases, a higher TyG index was significantly associated with an increased risk of dementia (OR = 1.14, 95% CI: 1.12–1.16), cognitive impairment (OR = 2.31, 95% CI: 1.38–3.86), and ischemic stroke (OR = 1.37, 95% CI: 1.22–1.54). For cardiovascular outcomes, the TyG index showed significant associations with an increased risk of heart failure (HF) (HR = 1.21, 95% CI: 1.12–1.30), atrial fibrillation (AF) (SMD = 1.22, 95% CI: 0.57–1.87), and hypertension (HTN) (RR = 1.52, 95% CI: 1.25–1.85). Conclusion The TyG index is a promising biomarker for screening and predicting various medical conditions, particularly those related to insulin resistance and metabolic disorders. However, the heterogeneity and methodological quality of the included studies suggest the need for further high-quality research to confirm these findings and refine the clinical utility of the TyG index. Graphical abstract